Challenges in Interfaith Marriage: Literature Review of Faith Values ​​and Their Implications for Families - Faizal, Liky; Fauzi, Moh. Yasir; Kamaruddin, Mohd Khairi; Qohar, Abd. (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
This study makes an original contribution by analyzing the challenges in interfaith marriages from the perspective of religious values ​​and their impact on the family. Although the topic of interfaith marriages has been widely discussed, this study focuses on identifying the challenges and dynamics related to religious values ​​that affect relationship stability and their implications for the family in a global context. This study uses a systematic and in-depth literature analysis approach to explore various relevant literature. The method used in this study is a literature review with a cluster analysis approach. Data were obtained through the use of publication tools such as Perish and VOSviewer to select 60 scientific articles related to the topic of interfaith marriage. There are 4 clusters produced, namely Cluster 1 (Red): in this cluster there are 13 items related to interfaith marriage and will be labeled "Marriage Rules with Different Cultures". Cluster 2 (Green): this cluster explains the label "Ethnic Acculturation in Marriage". Cluster 3 (Blue): This cluster is divided into 13 keywords items consisting of "Ethography in Marriage". Cluster 4 (Yellow): This yellow cluster consists of 7 keyword items, which will be labeled "Racist Actions against Children from Interfaith Marriages". The practical implications of this study provide insight for couples considering or in interfaith marriages to understand the challenges that may arise due to differences in beliefs. In addition, this study also suggests the need to increase tolerance and awareness of interfaith in society so that families in interfaith marriages can grow harmoniously.